A Comparative Study of Ssnack Consumption Behavior and Purchase Intention of Various Flavors Banana Chips from Consumers in Khon Kaen and Udon Thani Municipalities - Sungsriin, Manatchaya (Journal of Modern Learning Development, 2022)
The objectives of this research were to 1) explore new flavor ideas for banana chips, 2) compare snack consumption behavior and intention to purchase of various flavors banana chips of consumers in Khon Kaen and Udon Thani municipalities and 3) compare intention to purchase of various flavors banana chips of movie audiences in Khon Kaen and Udon Thani municipalitie. Internet survey of market snack product flavor and questionnaires survey of snack consumption behavior and intention to purchase of various flavors banana chips were conducted. The samples were 4 groups of consumers and movie audiences in Khon Kaen and Udon Thani municipalities. Sample size 120 each was determined by using continuous variable formular. Results find that there are 28 snack flavor ideas which were then used in the questionnaire. The most snack consumers buy is potato chips and more than 50 percent of consumers buy pop corn, shrimp kapok, cript pork skin, legume snack, banana chips, and Nori seaweet. Banana chips is then a snack buy by large group of consumers. There are only 6 flavors that consumers in Khon Kaen and Udon Thani municipalities probably would buy and 7 flavors from the movie audiences. There are no differences in snack consumption behavior and intention to purchase of various flavor banana chips amongst consumers in Khon Kaen and Udon Thani municipalities. And there are no differences in intention to purchase of various flavor banana chips amongst movie audiences in Khon Kaen and Udon Thani municipalities.